Conflict and performance in research teams: how principal investigator can influence this relationship - Foncubierta‐Rodríguez, María‐José; Martín‐Alcázar, Fernando; Perea‐Vicente, José‐Luis (R & D management, 2022)
The lack of consensus about overcoming the negative impact of conflict on team performance within research teams has become a challenge. Based on the complex context of knowledge‐intensive teams, this study examines the effect that a transformational leadership style of the Principal Investigator has on the relationship between team conflict and team performance. We propose an inverted U‐shaped relationship between research team conflict and research team performance, and examine the impact that the Principal Investigators’ transformational leadership has on this curvilinear relationship. Using survey data from 205 research teams, our results confirm both hypotheses. Actually, those PIs who apply the transformational leadership style will extend the positive conflict area, so, they will be able to manage a higher level of conflict in the research team. Our findings contribute to enhancing the understanding of the impact of conflict and the principal investigator’s transformational leadership style on team performance. Both theoretical and practical considerations are discussed.